1482. Changing Patterns of HIV-TB Coinfection Among Patients in a Public Health Department Ambulatory Care Setting: A 5-Year Experience from a US Metropolitan Area. (26th November 2018) - Addisu, Anteneh; Aslam, Sadaf; Holt, Douglas; Alrabaa, Sally; Casanas, Beata
Abstract: Background: HIV–TB coinfection leads to a complex set of synergistic interactions in the epidemiology, risk of acquisition, pathogenesis and prognosis of both infections. In the United States, the prevalence of HIV-TB coinfection has been around 6% for the past several years. We present here a 5-year experience at a public health department ambulatory care setting in Tampa, Florida, showing potentially changing patterns. Descriptive data and clinical aspect of coinfected patients is presented. Methods: A retrospective review of tuberculosis cases over the 5-year period ending December 2017 was performed. Those with HIV coinfection were included in the study. Clinical, microbiological and/or PCR based testing methods were used to make the diagnosis. SPSS was used to compile basic descriptive statistics Results: There were a total of 411 TB patients and 33 had HIV, an 8% prevalence of coinfection. The median age was 45 years (range 18–65). The male to female ratio was 21:12. Twenty-four percent (8/33) were homeless and 24% were foreign born. Only one patient admitted to using injection drugs while 27% (9/33) used non-injection illicit drugs. Forty-five percent (15/33) had TB symptoms such as fever, night sweats, weight loss and cough; the rest had radiographic abnormality which led to the diagnosis. Only 12% (4/33) had CT scan abnormality reported as cavitary or miliary while the rest had nonspecific infiltrates. Eighty-eight percent (29/33) had pulmonary TB while 6% had lymph node and 6% serosal (one pleural and one peritoneal) infections. Seventy-nine percent (29/33) were treated with a combination of daily observed and self-administered therapy. Twelve percent (4/33) did not complete therapy, or were lost to follow-up whereas one person was diagnosed post mortem thus not treated. Conclusion: The prevalence of HIV-TB coinfection in our cohort is slightly higher than the recent US average of 6% perhaps signifying the setting and demographics of our patient population. Our cohort was relatively older, most of them US born, and had predominantly pulmonary TB contrary to prior reports. These changing patterns may have been influenced by the overall older age of HIV patients in general or they could be indicators of underlying fundamental changes in the HIV-TB coinfection state at large. Additional study is needed to further elucidate this variance. Disclosures: All authors: No reported disclosures.